POSTPARTUM EDUCATION IN THE WORKING AREA OF THE TEBING COMMUNITY HEALTH CENTER - Nur Zahara Siddik; Ronny Sutanto (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2020)
Background : For early detection of complications in postpartum mothers, it is necessary to monitor the examination of postpartum mothers and increase the coverage of postpartum family planning by making at least 3 postpartum visits with time requirements, namely: the first postpartum visit during the period of 6 hours to 3 days after delivery, the second postpartum visit. within the 4th day to the 28th day after delivery, the third postpartum visit within the 29th to 42nd day after delivery. (MOH, 2012). The purpose of this study was to determine the education of postpartum mothers in the Tebing Community Health Center. Method : This study used a descriptive research design. The research was conducted in the working area of the Tebing Community Health Center. In the study, the population was postpartum mothers who were in the working area of the Tebing Community Health Center. In this study, researchers used purposive sampling technique, which is to determine a sample of the population based on specific objectives or according to the criteria desired by the researcher. The samples taken in this study were postpartum mothers in the working area of the Tebing Community Health Center. The method / technique of data collection was carried out by means of direct communication, namely by asking questions through written questionnaires with postpartum mothers who were in the working area of the Tebing Community Health Center. Univariate analysis is used to explain or describe the characteristics of each variable under study by presenting a description of the frequency distribution. Result : It is known that the majority of respondents' education is low as many as 31 respondents (70.5%) of 44 respondents Conclusion : It is known that the majority of respondents' education is low as many as 31 respondents (70.5%) of 44 respondents